Evaluation of Input-Output Efficiency of Sports Industry Based on SWOT-PEST Model - Huan Dong; Zhiguo Liu; Kai Kong; Tong Li; Qianli Ma (Journal of Mathematics)
This article takes the macro-environmental sports industry as the research object. Firstly, based on the development and characteristics of the sports industry, the article uses the principle of data envelopment analysis to analyze its input and output efficiency and finds out its current problems. In addition, the SWOT analysis method is used to conduct a comprehensive analysis of the external and internal environment influencing the efficiency of the sports industry and propose corresponding development countermeasures. Through the comparison of efficiency evaluation methods, the data envelopment analysis method is proposed to evaluate SWOT efficiency. Secondly, on the basis of pointing out the guiding ideology and basic principles of the evaluation system, four input indicators and four output indicators are specifically selected to form the SWOT input-output indicator system. Thirdly, we introduce the PEST model, focusing on its extended BCC model and use it to make empirical analysis of the SWOT efficiency of regions and provinces. The analysis results show that the efficiency of regional SWOT is not optimal and that there are problems such as input redundancy and insufficient output. Through further analysis, it is concluded that the main reason for the inefficiency of regional SWOT is the unreasonable SWOT input structure and insufficient output value of high-tech industries. We use the analytical framework of this method to clarify the current macro-competitive environment of the sports industry, and use the constructed index system to determine whether the sports industry environment in a region is good or bad. In the selection of indicators, we must carefully analyze their connotations, so that the evaluation index system can accurately evaluate the region’s sports industry environment.